Chapter Review of the Central and South Atlantic Shelf and Deep-Sea Benthos: Science, Policy, and Management - Bridges, Amelia E.H (Taylor & Francis, 2023)
The Central and South Atlantic represents a vast ocean area and is home to a diverse range of ecosystems and species. Nevertheless, and similar to the rest of the global south, the area is comparatively understudied yet exposed to increasing levels of multisectoral pressures. To counteract this, the level of scientific exploration in the Central and South Atlantic has increased in recent years and will likely continue to do so within the context of the United Nations (UN) Decade of Ocean Science for Sustainable Development. Here, we compile the literature to investigate the distribution of previous scientific exploration of offshore (30 m+) ecosystems in the Central and South Atlantic, both within and beyond national jurisdiction, allowing us to synthesise overall patterns of biodiversity. Furthermore, through the lens of sustainable management, we have reviewed the existing anthropogenic activities and associated management measures relevant to the region. Through this exercise, we have identified key knowledge gaps and undersampled regions that represent priority areas for future research and commented on how these may be best incorporated into, or enhanced through, future management measures such as those in discussion at the UN Biodiversity Beyond National Jurisdiction negotiations. This review represents a comprehensive summary for scientists and managers alike looking to understand the key topographical, biological, and legislative features of the Central and South Atlantic.